Burkholderia cenocepacia integrates cis-2-dodecenoic acid and cyclic dimeric guanosine monophosphate signals to control virulence - Yang, Chunxi (2020)
Quorum sensing (QS) signals are used by bacteria to regulate biological functions in response to cell population densities. Cyclic diguanosine monophosphate (c-di-GMP) regulates cell functions in response to diverse environmental chemical and physical signals that bacteria perceive. In Burkholderia cenocepacia, the QS signal receptor RpfR degrades intracellular c-di-GMP when it senses the QS signal cis-2-dodecenoic acid, also called Burkholderia diffusible signal factor (BDSF), as a proxy for high cell density. However, it was unclear how this resulted in control of BDSF-regulated phenotypes. Here, we found that RpfR forms a complex with a regulator named GtrR (BCAL1536) to enhance its binding to target gene promoters under circumstances where the BDSF signal binds to RpfR to stimulate its c-di-GMP phosphodiesterase activity. In the absence of BDSF, c-di-GMP binds to the RpfR-GtrR complex and inhibits its ability to control gene expression. Mutations in rpfR and gtrR had overlapping effects on both the B. cenocepacia transcriptome and BDSF-regulated phenotypes, including motility, biofilm formation, and virulence. These results show that RpfR is a QS signal receptor that also functions as a c-di-GMP sensor. This protein thus allows B. cenocepacia to integrate information about its physical and chemical surroundings as well as its population density to control diverse biological functions including virulence. This type of QS system appears to be widely distributed in beta and gamma proteobacteria.